2013
DOI: 10.1109/lpt.2013.2283744
|View full text |Cite
|
Sign up to set email alerts
|

Digital Coherence Enhancement Enabling 6-GBd DP-64QAM Using a 1.4-MHz Linewidth Laser

Abstract: This letter demonstrates the possibility of using digital coherence enhancement-a means of estimating and digitally compensating local oscillator laser phase noise using a secondary, low speed coherent receiver-to enable the reception of high order quadrature amplitude modulation (QAM) using a monolithically integrated tunable semiconductor laser as local oscillator. We show that this coherence enhancement technique compensates both the Lorentzian and non-Lorentzian distributed phase noise of this laser, enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…[ [26][27][28][33][34][35][36]. Among these methods, the digital coherence enhancement shows the best performance [26,36], while it requires a complicated hardware implementation to measure the LO laser phase fluctuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ [26][27][28][33][34][35][36]. Among these methods, the digital coherence enhancement shows the best performance [26,36], while it requires a complicated hardware implementation to measure the LO laser phase fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…Among these methods, the digital coherence enhancement shows the best performance [26,36], while it requires a complicated hardware implementation to measure the LO laser phase fluctuation. By contrast, EEPN does not exist in the coherent transmission systems using optical dispersion compensation, such as dispersion compensating fibers (DCFs) and dispersion compensating modules (DCMs) [18,19,22,25,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The second arm was passed into the differential phase noise measurement setup, which consisted of a 90°optical hybrid, balanced receivers and a two channel optical sampling oscilloscope. An additional delay (τ ) was added to one of the optical hybrid arms to create an interferometer, with the maximum frequency (1/τ ) of the measurement technique inversely proportional to the delay, as described in [7]. Finally, a noise loading stage was employed to vary the received OSNR for BER measurements.…”
Section: Fast Wavelength Switching Digital Coherent Receivermentioning
confidence: 99%
“…Several techniques for transmitter laser phase noise reduction have previously been demonstrated [4], [5], while Secondini et al, demonstrated a ten-fold phase noise reduction of a LO laser in a digital coherent receiver [6]. In this letter, the digital coherence enhancement technique proposed in [6] was adapted [7] and applied to a fast wavelength switching DS-DBR LO laser. It is the first demonstration, to the best of our knowledge, of a fast wavelength switching DP-16QAM digital coherent burst mode receiver, that utilizes a commercially available DBR based tunable laser as the LO.…”
mentioning
confidence: 97%
“…This is achieved by replacing the 50/50 output coupler of the interferometer with an optical 90 • hybrid coupler in order to perform in-phase (I) and quadrature (Q) detection of the mixed optical fields [ figure 1(b)]. This is commonly done in the field of optical communications [20,21,22]. However, this idea has not yet significantly diffused to the optical metrology community and has not been applied for the characterization of highly-stable lasers.…”
Section: Introductionmentioning
confidence: 99%